2017
DOI: 10.1093/jisesa/iex040
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Quercetin in the Temporal Regulation of Redox Homeostasis in Drosophila melanogaster

Abstract: Numerous biological processes are governed by the biological clock. Studies using Drosophila melanogaster (L.) are valuable that could be of importance for their effective applications on rodent studies. In this study, the beneficial role of quercetin (a flavonoid) on H2O2 induced stress in D. melanogaster was investigated. D. melanogaster flies were divided into four groups (group I – control, group II – H2O2 (acute exposure), group III – quercetin, and group IV – quercetin + H2O2 treated). Negative geotaxis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 76 publications
(94 reference statements)
0
13
0
Order By: Relevance
“…Hesperidin on the other hand, display antioxidative properties by scavenging of free radicals (Garg et al, 2001), restrain free radical synthesis and the distribution of free radical reactions through the chelation of metal (iron and copper) ions (Andjelković et al, 2006), suppresses the superoxide‐derived Fenton reaction (Mladenka et al, 2011) and augment endogenous antioxidative defense system (Poetini et al, 2018). Previous studies had indicated that treatment with flavonoids could reverse the disturbed rhythmicity of antioxidants and biochemical indices (Subramanian et al, 2017). The data of the present study generally substantiate the previously reported finding of the rhythmic proteome profiling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hesperidin on the other hand, display antioxidative properties by scavenging of free radicals (Garg et al, 2001), restrain free radical synthesis and the distribution of free radical reactions through the chelation of metal (iron and copper) ions (Andjelković et al, 2006), suppresses the superoxide‐derived Fenton reaction (Mladenka et al, 2011) and augment endogenous antioxidative defense system (Poetini et al, 2018). Previous studies had indicated that treatment with flavonoids could reverse the disturbed rhythmicity of antioxidants and biochemical indices (Subramanian et al, 2017). The data of the present study generally substantiate the previously reported finding of the rhythmic proteome profiling.…”
Section: Discussionmentioning
confidence: 99%
“…The flies were categorized into four groups (Group I: wild‐type/control; Group II: rotenone‐treated; Group III: rotenone and hesperidin treated; and Group IV: hesperidin‐treated flies). Rotenone (70 mg/unit media; 1 unit medium = 300 ml) and hesperidin (0.1 g/100 ml medium) were administered to adult male flies (10 days old) for 7 days through media (Arumugam, Jayapalan, Abdul‐Rahman, Hashim, & Subramanian, 2018; Subramanian, Kaliyamoorthy, Jayapalan, Abdul‐Rahman, & Haji Hashim, 2017; Subramanian, Prasanna, Jayapalan, Abdul Rahman, & Hashim, 2014). On the seventh day, male flies ( n = 15/group/time point) were collected from four groups at 6 h intervals (00:00, 06:00, 12:00, and 18:00) continuously over the 24‐h period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, hesperidin up-regulates HO-1 expression through increased nuclear factor erythroid 2-related factor (Nrf2) signaling [46].The anti-inflammatory effect of HES has been chiefly associated with its antioxidant activity and ability to inactivate the proinflammatory cascade initiated by free radicals. It inhibits of nuclear factor kappa B (NF-κB) expression that triggers pro-inflammatory genes synthesis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Daflon, a dietary supplement, is also a source for hesperidin [8].Hesperidin is a strong antioxidant and one of naturally occurring iron chelators [9]. In addition, it suppresses inflammation [10].…”
Section: Introductionmentioning
confidence: 99%